American horror story. Asylum. The complete second season [videorecording (DVD)] - Quinto, Zachary; Fiennes, Joseph, 1970-; Paulson, Sarah, 1974-; Peters, Evan, 1987- (Twentieth Century Fox Home Entertainment, 2013)
Step inside a madhouse of horror and experience the chilling new incarnation of TV's most daringly provocative series. The sins of the past haunt the present at the notorious Briarcliff home for the criminally insane, ruled with an iron fist by Sister Jude. Forbidden desire and terrifying evil lurk around every corner, from alien abduction to demonic possession to a skin-wearing psychopath known as 'Bloody Face.'